2011
DOI: 10.24841/fa.v20i1-2.359
|View full text |Cite
|
Sign up to set email alerts
|

WATER TEMPERATURE EFFECTS ON GROWTH, FEED UTILIZATION AND SURVIVAL OF BLACK PACU (Colossoma macropomum) FINGERLINGS

Abstract: Ectothermic organisms normally live within a specific interval of thermal variation and life outside of that interval can be extremely difficult or lethal. Aquacultural use of black pacu Colossoma macropomum has expanded to diverse areas with various climatic conditions. In the past few years, practical aquafeeds have been evaluated striving to improve the performance of Amazonian fish, but there is little information regarding environmental effects on black pacu growth, feed intake and utilization. This lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Lapointe et al 52 and Amanajás et al (in preparation) found increased mortality and decreased specific growth rate, respectively, at 15 and 21 days of cultivation at 35°C. According to Chu‐Koo et al, 53 temperatures above 32°C increase consumption, decrease food conversion efficiency and can impair species growth during 21 days of cultivation. However, the effects of temperature seem to be modulated by simultaneous exposure to darkness.…”
Section: The Relationship Between Temperature and Tambaquimentioning
confidence: 99%
“…Lapointe et al 52 and Amanajás et al (in preparation) found increased mortality and decreased specific growth rate, respectively, at 15 and 21 days of cultivation at 35°C. According to Chu‐Koo et al, 53 temperatures above 32°C increase consumption, decrease food conversion efficiency and can impair species growth during 21 days of cultivation. However, the effects of temperature seem to be modulated by simultaneous exposure to darkness.…”
Section: The Relationship Between Temperature and Tambaquimentioning
confidence: 99%